PENGAJIAN AL-QUR’AN DALAM TRADISI PERNIKAHAN PADA MASYARAKAT SUNDA: KEBERLANGSUNGAN DAN PERUBAHAN - Dadan Rusmana (Fakultas Adab dan Humaniora UIN Sunan Gunung Djati Bandung, 2020)
The purpose of this paper is to explain about some forms of al-Qur'an recitation activities in the tradition of marriage among Sundanese-Muslim communities, with the diversity of moments, personal, ways, and religious meanings. The problem is related to several things, namely 1) the forms of recitating the Qur'an carried out by the Sundanese-Muslim community in the tradition of marriage; 2) religious meaning of the tradition of Qur’anic recitation in the Sundanese-Muslim community; 3) the change of Qur’anic recitation activities influenced by internal and external factors. The theory used is the theory of the rite of Radcliffe Brown and the commodification of Islam from Greg Fealy. The domain of this research is in the study of cultural anthropology with an ethnographic approach. The results of this study indicate that the diversity of the tradition of the reciting the Qur’an carried out adjusted to the moment, economic level, individual abilities, and the environment. Sustainability and change occur because of the internal and external influences in implementing this tradition. From the point of view of meaning, this tradition shows identity, social stratification, and the commodification of the Qur’an recitation in the public sphere. This research has implications for the importance of increasing the quality of ritual understanding, rather than merely formality formal rituals.